DIURNAL VARIATION IN THE CATCHES OF DEMERSAL FISHES IN THE NORTH WEST REGION OF BAY OF BENGAL DURING 1959-60 - Rao, T Appa; Moorthi, B Krishna (Indian Journal of Fisheries, 2011)
During the pericxl November 1959-Ootober 1960, the Government of Indiatrawler M. T. Ashok carried out exploratory trawling for demersal fishes, bothduring day and night, off the coasts of Andhra and Orissa between latitudes17°-40' to 20°-10' N and in depths ranging from 5 to 64 metres. Six major groups offishes viz., sharks and skates, rays, catflshes miscellaneous big and small fishes andprawns in the catches showed diurnal variations. The catches of sharks, skates,miscellaneous fish and catfish were heavier during the day than night, irrespectiveof the area of capture and depth. Prawns and rays, however, yielded bettercatches at night.No definite trends could be seen in the seasonal variations of the abovesix groups in 17°-40' N and 18°-10' N latitude zones and also at two depth-rangesof 35-44 m and 45-54 m. Further, analysis was made of the seasonal variationsof the six groups at two depth-ranges 35-44 m and 45-54 m, but no definite trendson their abundance could be discerned.